A collaborative study to establish the 1st WHO International Standard for Epstein–Barr virus for nucleic acid amplification techniques. Issue 5 (September 2016) - Fryer, Jacqueline F.; Heath, Alan B.; Wilkinson, Dianna E.; Minor, Philip D.; ,
Abstract: Variability in viral load measurements using nucleic acid amplification techniques (NAT) has a significant impact on the management of Epstein–Barr virus (EBV)-associated diseases, and has highlighted a need for standardisation of these measurements. The aim of this collaborative study was to evaluate the suitability of a range of candidate reference materials to harmonise EBV viral load measurements in a wide range of NAT assays. Candidate materials included lyophilised and liquid whole virus preparations of the EBV B95-8 strain, and preparations of Namalwa and Raji cells. Variability between the individual laboratory mean estimates for each candidate was 2.5 log10 copies/mL. The agreement between laboratories was improved when the potency of each candidate was expressed relative to the lyophilised B95-8 preparation. The results of the study indicate the suitability of this candidate as the 1st WHO International Standard for EBV for NAT. It was established in October 2011 by the WHO's Expert Committee on Biological Standardisation with an assigned potency of 5 × 10 6 International Units (IU) (NIBSC code 09/260). It is intended to be used for the calibration of secondary reference materials, used in EBV NAT assays, in IU, thereby improving the comparability of patient viral load measurements.